The performance teacher evaluation model in Mexican educational reform - Graciela Cordero; Coral González (Arizona State University, 2016)
The aim of this paper is to analyze and graph the performance teacher evaluation model within the framework of Mexican educational reform in order to clarify its elements, the relationships between them, and the structure that articulates them. The core content is divided into four sections. First, the changes in the teaching profession are presented within the context of Latin America. In the second section, the Mexican educational reform is described. In the third, the process of teacher evaluation is explained. The fourth section shows and describes the performance evaluation model generated from the analysis of the central texts of the reform. Finally, the model is discussed and reflections by way of conclusion are presented.